2022
DOI: 10.1038/s41598-022-19969-w
|View full text |Cite
|
Sign up to set email alerts
|

Ionic complexation improves wound healing in deep second-degree burns and reduces in-vitro ciprofloxacin cytotoxicity in fibroblasts

Abstract: The development of new treatments capable of controlling infections and pain related to burns continues to be a challenge. Antimicrobials are necessary tools, but these can be cytotoxic for regenerating cells. In this study, antibiotic-anesthetic (AA) smart systems obtained by ionic complexation of polyelectrolytes with ciprofloxacin and lidocaine were obtained as films and hydrogels. Ionic complexation with sodium alginate and hyaluronate decreased cytotoxicity of ciprofloxacin above 70% in a primary culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Regarding the presence of antimicrobial agents such as antibiotics, anti-inflammatory drugs, and inorganic NPs in the delivery system, the concentration-dependent reduction in cell viability has been reported in prior studies. [62][63][64] Van Meurs et al found that OCT concentration below 2 × 10 −3 mg mL −1 does not affect cellular viability, 65 while Klaue et al decreased this amount to 5 × 10 −4 mg mL −1 and confirmed the ability to provide significant antimicrobial activity at the same concentration. 66 Our 100% extracts exhibited much higher OCT concentration (1.2 × 10 −2 mg mL −1 ).…”
Section: Biomaterials Science Papermentioning
confidence: 98%
“…Regarding the presence of antimicrobial agents such as antibiotics, anti-inflammatory drugs, and inorganic NPs in the delivery system, the concentration-dependent reduction in cell viability has been reported in prior studies. [62][63][64] Van Meurs et al found that OCT concentration below 2 × 10 −3 mg mL −1 does not affect cellular viability, 65 while Klaue et al decreased this amount to 5 × 10 −4 mg mL −1 and confirmed the ability to provide significant antimicrobial activity at the same concentration. 66 Our 100% extracts exhibited much higher OCT concentration (1.2 × 10 −2 mg mL −1 ).…”
Section: Biomaterials Science Papermentioning
confidence: 98%